Well-being challenges of palm oil smallholders community - Noordeyana Tambi,; Er, Ah Choy; Nur Hafizah Yusoff,; Azlan Abas,; Ummu Liyana Halim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysian government has introduceda commercial palm oil agriculture programme to enhance personal, family and at the same time increase national income. The programme aims to increase of smallholders not only with the economic growth of families and communities, but also promote the physical. The basic prerequisite about oil palm cultivation is good land for cultivation. Apart from access to farms which also pay an important role in facilitating farm management. The impact of the development will build more employment opportunities with good basic services, growth of various types of growth of various types of industry, housing, school facilities and other basic facilities. Therefore, the purpose of this paper is to identify the challenges to improve the well-being of smallholder’s palm oil communities in Malaysia. Discussions on the challenges to palm oil smallholders focus on land shortages, lack of access to credit and loans, lack of improved planting materials, lack of training and skills, lack of processing facilities, high fertilizer prices, technological expertise and soil fertility challenges. Meanwhile, discussions on community well-being focus on the economic, social and environmental aspects of smallholder palm oils. This discussion of challenges and well-being is also linked to the Sustainable Development Goals (SDG) for future planning of the palm oil smallholder community.